2022
DOI: 10.3389/fonc.2022.984014
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical recurrence factors and outcome after radical nephroureterectomy for upper tract urothelial carcinoma: Multivariate analysis with propensity score matching

Abstract: ObjectiveThe risk factors for intravesical recurrence (IVR) after radical nephroureterectomy (RNU) in patients with upper tract urothelial carcinoma (UTUC) remain inconsistent and unclear. Thus, the risk factors of IVR after RNU and the prognostic significance of the risk indicators were explored herein.MethodsWe retrospectively analyzed UTUC patients upon RNU in our center from January 2009 to December 2019. After propensity score matching, 139 patients were included in this study. Univariate and multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Specifically, regarding BR after RNU, a meta-analysis by Seisen et al reported three distinct domains of significant predictors for BR ( 13 ). First, patient-specific factors are male gender, history of non-muscle invasive bladder cancer (NMIBC), preoperative chronic kidney disease, and smoking at the time of diagnosis ( 13 - 15 ). Second, the tumor-specific factors include preoperative urine cytology positive for abnormal urothelial cells, ureteral tumor location, tumor multifocality, invasive pT stage, tumor necrosis, and presence of carcinoma in situ ( 13 , 14 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, regarding BR after RNU, a meta-analysis by Seisen et al reported three distinct domains of significant predictors for BR ( 13 ). First, patient-specific factors are male gender, history of non-muscle invasive bladder cancer (NMIBC), preoperative chronic kidney disease, and smoking at the time of diagnosis ( 13 - 15 ). Second, the tumor-specific factors include preoperative urine cytology positive for abnormal urothelial cells, ureteral tumor location, tumor multifocality, invasive pT stage, tumor necrosis, and presence of carcinoma in situ ( 13 , 14 , 16 ).…”
Section: Introductionmentioning
confidence: 99%